The Influence of Financial Decisions on the Value of the Indonesian Railroad Services Company Persero Bandung - Hamiru Hamiru (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
PT. Kereta Api Indonesia on increasing company value during 2019-2021. and (b) to determine the effect of the implementation of the funding policy implemented by the management of PT. Kereta Api Indonesia on increasing company value during 2019-2021. The objects studied in this study are companies engaged in the transportation services sector for Indonesian Railways services. PT. Kereta Api Indonesia is an Indonesian state-owned enterprise that provides rail transportation services. PT services The data source for this research is secondary data. Secondary data is data taken in the form of data that has been processed in the form of reports that have been prepared by competent agencies or institutions in the form of reports, books or written materials related to the topic to be studied. The results of this research, namely the results of this study, can be concluded that: (a) Pricing Earning Share, Debt to Equity Ratio and Dividend Pay Out Ratio have no significant effect on firm value. (b) The hypothesis says that the Pricing Earning Share, Debt to Equity Ratio and Dividend Pay Out Ratio have no significant effect on the value of the rejected company; (c) Variations in book value per share, large capital to guarantee debt and dividend distribution policies do not affect how much the value of PT. Kereta Api Indonesia through Price to Book Value (PBV).